Quelle lesbienne êtes-vous? - Causse, Michèle (Parole de lesbiennes, 1996)
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétéronormativité; identités LGBTQIA2+; inégalités; lesbianisme; paris; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Bisexualité: le dernier tabou - Mendès-Leite, Rommel; Deschamps, Catherine; Proth, Bruno-Marcel (Calmann-Lévy, 1996)
A partir de nombreux témoignages, ce livre dresse un portrait des bisexuels dans leur infinie variété, leur histoire, leur quotidien.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Queer theory/sociology - Seidman, Steven (Twentieth-century social theory, 1996)
Bringing together some of the classic sociological statements and the new sociology of homosexual desire, this book points to new synthetic approaches to queer studies. It aims to productively engage the pioneering work of queer theorists.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; premier cycle; périodes historiques; queer; sciences humaines; soc2014; sociologie; sofia; thématiques

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques